2023
DOI: 10.3390/vaccines11020327
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Evidence on Association between Iron Deficiency and COVID-19 Vaccine-Induced Neutralizing Humoral Immunity

Abstract: Iron is a crucial micronutrient for immunity induction in response to infections and vaccinations. This study aimed to investigate the effect of iron deficiency on COVID-19-vaccine-induced humoral immunity. We investigated the effectiveness of COVID-19 vaccines (BNT162b2, mRNA-1273, and ChAdOx nCov-2019) in iron-deficient individuals (n = 63) and provide a side-by-side comparison to healthy controls (n = 67). The presence of anti-SARS-CoV-2 spike (S) and anti-nucleocapsid (NP) IgG were assessed using in-house … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…[14][15][16][17][18][19][20][21][22][23][24][25] Three studies have reported no association between serum iron or selenium status, as well as concentrations of total zinc, and antibody concentrations or titers in response to COVID-19 vaccinations. [14][15][16] Nine studies have reported the associations between serum vitamin D concentrations or status (sufficient, deficient, or insufficient) and humoral responses following COVID-19 vaccinations, yet inconsistent conclusions have been reached. [17][18][19][20][21][22][23][24][25] Investigations into the influence of micronutrients on antibody binding affinity and neutralizing capacity against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), crucial parameters for immune protection, are virtually non-existent.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[14][15][16][17][18][19][20][21][22][23][24][25] Three studies have reported no association between serum iron or selenium status, as well as concentrations of total zinc, and antibody concentrations or titers in response to COVID-19 vaccinations. [14][15][16] Nine studies have reported the associations between serum vitamin D concentrations or status (sufficient, deficient, or insufficient) and humoral responses following COVID-19 vaccinations, yet inconsistent conclusions have been reached. [17][18][19][20][21][22][23][24][25] Investigations into the influence of micronutrients on antibody binding affinity and neutralizing capacity against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), crucial parameters for immune protection, are virtually non-existent.…”
Section: Introductionmentioning
confidence: 99%
“…Only a limited number of studies with sample sizes ranging from 97 to 73 254 participants have investigated the associations between circulating concentrations of micronutrients, particularly those involved in immune regulation, and humoral immune responses as well as protection following inoculation with COVID-19 vaccines. [14][15][16][17][18][19][20][21][22][23][24][25] Three studies have reported no association between serum iron or selenium status, as well as concentrations of total zinc, and antibody concentrations or titers in response to COVID-19 vaccinations. [14][15][16] Nine studies have reported the associations between serum vitamin D concentrations or status (sufficient, deficient, or insufficient) and humoral responses following COVID-19 vaccinations, yet inconsistent conclusions have been reached.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation